A Review on Smart Traffic Management System. Issue 1 (April 2021) - Indhiradevi, P; Saravanakumar, P; Varsha, R; Shahithya, S; Naveen Prabhu, S
Abstract: Traffic congestion could be a condition in transport where it has huge crowds, slows the speed of vehicles and even it increases the vehicular lengths. Traffic congestion on city road networks has increased rapidly, since the 1950s. When the traffic demand is great then the interaction between the vehicles reduces the speed of the traffic and finally results in traffic congestion. To overcome such circumstances in present scenario, smart traffic management system can be initiated and we are in study to find a solution to make traffic free city. This system helps in monitoring the traffic signals and flow of vehicles by means of image processing with CCTV cameras. CCTV cameras help in image processing and identifying the number of vehicles passing in the road surface. It helps in abating the traffic congestion in the road and fuel consumption of the automobiles. Sensors are used for detecting the number of vehicles and speed. By coordinating the CCTV cameras and sensors the collected information can be sent to Variable Message Sign (VMS) Boards. This board displays the information regarding traffic to the road users. It helps in diverting and altering the roads at the earliest where the waiting time is reduced. Though the waiting time is reduced, fuel is consumed automatically. Therefore, reduction in the fuel consumption helps to control the air pollution. By creating the control system and detecting the problems faced in the road, traffic congestion can be reduced and provide traffic free environment. As we face rapid growth of our country's population, smart traffic management system provides people to have smooth transportation network which would find a way to reach their destination soon and make their journey better forever.